2021
DOI: 10.18549/10.18549/pharmpract.2021.1.2201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a national policy advocating rational drug use on decreases in outpatient antibiotic prescribing rates in Thailand

Abstract: Objective: This study examined the effects of a national policy advocating rational drug use (RDU), namely, the ‘RDU Service Plan’, starting in fiscal year 2017 and implemented by the Thai Ministry of Public Health (MOPH), on trends in antibiotic prescribing rates for outpatients. The policy was implemented subsequent to a voluntary campaign involving 136 hospitals, namely, the ‘RDU Hospital Project’, which was implemented during fiscal years 2014-2016. Methods: Hospital-level antibiotic prescribing rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In our study, the most frequently used oral antibiotics in outpatients were amoxicillin, then sulfasalazine followed by trimethoprim/sulfamethoxazole. A study in Thailand by Waleekhachonloet et al 30 examined the effects of a national policy encouraging rational antibiotic prescribing rates in OPD and found that the policy was effective in decreasing antibiotic prescription for questionable cases. The study by Hashimoto et al 31 found that outpatient antibiotic prescription in Japan were high for acute respiratory or gastrointestinal infections, for which the prescription of antibiotics is generally not indicated, but intervention should be by antimicrobial stewardship.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the most frequently used oral antibiotics in outpatients were amoxicillin, then sulfasalazine followed by trimethoprim/sulfamethoxazole. A study in Thailand by Waleekhachonloet et al 30 examined the effects of a national policy encouraging rational antibiotic prescribing rates in OPD and found that the policy was effective in decreasing antibiotic prescription for questionable cases. The study by Hashimoto et al 31 found that outpatient antibiotic prescription in Japan were high for acute respiratory or gastrointestinal infections, for which the prescription of antibiotics is generally not indicated, but intervention should be by antimicrobial stewardship.…”
Section: Discussionmentioning
confidence: 99%
“…The five years of Thailand’s national strategic plan on antimicrobial resistance have not been fully reported. There is only a report on decreasing the level of and trend in antibiotic prescribing rates during the years 2017–2019 from the RDU Service Plan [ 31 ]. Reports should evaluate not only the decrease in antimicrobial consumption but also the incidence and prevalence of AMR compared with the antibiotics prescription or consumption rate.…”
Section: Discussionmentioning
confidence: 99%
“…These differences among various studies are likely due to differences in national health care systems, culture, and the level of the hospital in which a given study was conducted. GPs in Srinagarind Hospital are mostly young physicians who graduated during the national rational drug use (RDU) campaign [ 8 ]. However, residents in fields other than internal medicine may be more focused on improving their specialized skills and knowledge than on general topics.…”
Section: Discussionmentioning
confidence: 99%
“…Although antibiotics are available over-the-counter in pharmacies in Thailand [ 6 ], public and private health care facilities still provide the majority (70.3%) of such medications [ 7 ]. The pre-intervention prescription rate was approximately 45% in patients with URI (despite the national target being under 20%) [ 8 ], and the most frequently prescribed antibiotics were amoxicillin and co-amoxiclav [ 9 ]. A recent study showed inappropriate antibiotic prescription to be common in URI [ 10 ].…”
Section: Introductionmentioning
confidence: 99%